'Trembling and groaning depart': *Disputing the devil in Christian baptism. (September 2015) - French, Anna
Recent Church of England discussions have debated the appropriateness of mentioning the devil during baptism. Asking godparents to shun Satan and his works on behalf of the newly baptized may, it has been suggested, confuse members of the congregation. This article explores these issues, arguing that controversies surrounding the role of the devil at the font are not new. Protestant Reformers in the sixteenth century were similarly wary of mentioning his name or misleading spectators. For early modern theologians, the issue was less about 'putting off' those sitting in pews and more about avoiding the implication that baptism was a magical seal that would protect the participant from the devil's works without question. This article will consider contemporary and early modern disputes surrounding the devil and baptism.